2006
DOI: 10.1002/elan.200603655
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polycyclic Aromatic Hydrocarbons on the Electrochemical Responses of a Ferricyanide Probe at Template‐Modified Self‐Assembled Monolayers on Gold Electrodes

Abstract: The impact of polycyclic aromatic hydrocarbons (PAHs) on the electrochemical responses of a ferricyanide probe using gold electrodes coated with template-containing self-assembled monolayers (SAMs) was investigated using cyclic voltammetry and square-wave voltammetry. The thiolated compounds that were used to form SAMs included 1-hexadecanethiol, 11-mercapto-undecanoic acid, 11-mercaptoundecanol, and (3-mercaptopropyl) trimethoxysilane (MPTS). When the SAMs were formed from 1-hexadecanethiol or 11-mercapto-und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The cross‐linked pyrene imprinted monolayer on gold showed selectivity toward pyrene compared with the larger benzo[α]pyrene. (Luo et al ., ).…”
Section: Monolayer Templatingmentioning
confidence: 99%
See 3 more Smart Citations
“…The cross‐linked pyrene imprinted monolayer on gold showed selectivity toward pyrene compared with the larger benzo[α]pyrene. (Luo et al ., ).…”
Section: Monolayer Templatingmentioning
confidence: 99%
“…The cross-linked pyrene imprinted monolayer on gold showed selectivity toward pyrene compared with the larger benzo[a]pyrene. (Luo et al, 2006). Matsumoto et al (2008) prepared a cholesterol imprinted monolayer by immersing a clean gold electrode in an ethanol solution containing 20mM cholesterol and 0.1mM of stearylmercaptan for 30min.…”
Section: Molecularly Imprinted Monolayers On Gold Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kirsch et al [18] prepared molecularly imprinted polystyrene coatings on screen-printed carbon electrodes for the detection of 1-hydroxypyrene. Luo et al [19] reported the detection of pyrene using molecularly imprinted SAMs immobilized onto gold electrodes.…”
Section: Introductionmentioning
confidence: 99%